FIGURE 4 in A new species of Eryx (Serpentes: Erycidae) from Iran - Eskandarzadeh, Naeimeh; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Zargan, Jamil; Hajinourmohamadi, Ashkan; Nazarov, Roman A.; Sami, Soheil; Rajabizadeh, Mahdi; Nabizadeh, Hossein; Navaian, Majid (Zenodo, 2020)
FIGURE 4. The paratype specimen of Eryx sistanensis sp. nov. (HCHSU 8487). (A) The head, (B) dorsal view, (C) ventral view. : Published as part of Eskandarzadeh, Naeimeh, Rastegar-Pouyani, Nasrullah, Rastegar-Pouyani, Eskandar, Zargan, Jamil, Hajinourmohamadi, Ashkan, Nazarov, Roman A., Sami, Soheil, Rajabizadeh, Mahdi, Nabizadeh, Hossein & Navaian, Majid, 2020, A new species of Eryx (Serpentes: Erycidae) from Iran, pp. 182-192 in Zootaxa 4767 (1) on page 187, DOI: 10.11646/zootaxa.4767.1.8, http://zenodo.org/record/3770697